Enhancing Tourism Village Performance Through Maximizing Social Capital and Financial Literacy: A Systematic Literature Review - Suputra, Gusti Alit; Purbawangsa, Ida Bagus Anom; Rahyuda, Henny; Dewi, Sayu Ketut Sutrisna (International Journal of Social Science and Business, 2024)
The management of tourism villages, particularly in rural areas, remains a challenge and requires comprehensive strategies and policies for their development. Managers’ social capital and financial literacy are important for improving the performance of tourism villages, but related data are still limited. Through a systematic literature review, this study investigates the role of social capital and financial literacy in influencing the performance of tourism villages. The literature search and analysis of the included articles were guided by PRISMA. This study involves original articles discussing the role of social capital and financial literacy, open access, published between 2010 and 2022, indexed in SINTA (Science and Technology Index) and scopus (Quartile Q1-Q4) and in Indonesian or English. This review explored the use of social model concepts and financial literacy in tourism villages, the methodology used, and the main findings. The results show that social capital and financial literacy significantly affect the performance of tourism villages. The synergy between social capital mechanisms and financial literacy can create a conducive environment for tourism development and success in villages. Social capital plays a role in building trust and sustainable cooperation between tourism sectors, social connections in facilitating the exchange of tourism information and resources, and increasing community capacity and involvement in tourism implementation. Financial literacy plays a role in equipping tourism village managers with efficient financial management, developing tourism-based entrepreneurship, and ensuring inclusiveness and sustainability. Tourism villages are characterized by their growth, development, and performance. The implication of this study is that social capital and financial literacy directly and indirectly improve the performance of tourism villages.